ENTREPRENEURSHIP CULTURE AND ENTREPRENEURSHIP COURSE: DO THEY SUPPORT STUDENTS' ENTREPRENEURSHIP INTENTION? - Elsye Tandelilin; Noviaty Kresna Darmaetiawan; Ivana Krisantana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2016)
The aim of this research is to examine the effect of entrepreneurship culture (perceived appropriateness, perceived consistence, and perceived effectiveness) and entrepreneurship education (course) toward entrepreneurship intention on the college students in Faculty of Business and Economics, University of Surabaya. This quantitative research uses cross-sectional survey design, with Likert scale measurement. This research uses primary data obtained through questionnaires. The total number of samples used were 238 respondents. Methods of data analysis using multiple linear regression. The results showed that the correlation and regression analyses support the hypotheses that the entrepreneurship culture and the entrepreneurship education jointly relate to entrepreneurial intentions. However, the variable of entrepreneurship education (course) separately not relate to entrepreneurial intentions while entrepreneurship culture has positive effect on entrepreneurial intentions.